A Chronic Glottic Foreign Body Diagnosed by Radiograph after 9 Months of Symptoms - Laura H. Swibel Rosenthal; Virginia Smith-Bronstein; Santino Cervantes; James W. Schroeder (Case Reports in Pediatrics)
A six-year-old girl presented to an emergency room after describing choking on a rubber band. She was in no distress and was discharged. Over the course of the next 9 months, she had numerous outpatient and emergency room visits due to intermittent stridor, difficulty breathing, and hoarseness. Eventually, dedicated airway films revealed a laryngeal foreign body. During rigid bronchoscopy, a two-centimeter rubber band was discovered in the larynx. It extended from the supraglottis, through the glottis, and into the subglottis. It was successfully removed. The patient was asymptomatic 24 hours later. This case highlights the appropriate evaluation and management of a child with stridor.